Stimulasi lima aspek perkembangan anak usia dini - Lilla, Khusbatul (Maliki Interdisciplinary Journal, 2024)
Education in early childhood is very important, namely to prepare children for further education. In educational institutions, the aim is to help 5 aspects of development in children which consist of language development, cognitive development, social emotional development, physical motor development and also the development of religious and moral values. Apart from formal institutions, these five aspects can also be stimulated by parents or people around the child, so that these 5 aspects develop more optimally and optimally.